IMPLEMENTASI KEBIJAKAN BANTUAN SISWA MISKIN DI SEKOLAH MENENGAH ATAS NEGERI 1 WATANG PULU KABUPATEN SIDENRENG RAPPANG - Suryanti Baddura (PRAJA: Jurnal Ilmiah Pemerintahan, 2017)
This study aims to determine how the implementation of poor student assistance policies at State High School 1 Watang Pulu, Sidenreng Rappang Regency and the factors that influence the implementation of poor student assistance policies at State High School 1 Watang Pulu, Sidenreng Rappang Regency. The type of research that the author uses is descriptive and the research method used in this study is the method of observation, interviews, questionnaires and documentation which is carried out systematically based on the research objectives. The population in this study were students of SMA Negeri 1 Watang Pulu, Sidenreng Rappang Regency who received 81 students from the Poor Student Assistance (BSM) and the sampling technique took the entire existing population, which was 81 people. The basis for sampling is saturated if the subject is less than 100, then it is better to take all, so that the research is a population study. While the informants in this study were principals, teachers, and students and parents of students at the State High School 1 Watang Pulu, Sidenreng Rappang Regency. The results of this study indicate that the implementation of the Poor Student Assistance Policy at the State High School 1 Watang Pulu, Sidenreng Rappang Regency has been going very well, it can be seen from several indicators, namely communication, resources, disposition (bureaucratic attitude and implementers) and organizational structure. While the factors that influence the poor student assistance program are planning greatly affects 81.75%, organizing greatly affects 80%, coordination greatly affects 95% and evaluation has been carried out greatly affects 93%.